2020
DOI: 10.9734/ijbcrr/2020/v29i930223
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Modulatory Effect of Methanol Extract of Daniellia oliveri (ROLFE) Leaves on Mitochondrial Membrane Permeability Transition (MPT) Pore

Abstract: Background: Mitochondrial-mediated cell death begins with opening of mitochondrial membrane permeability transition (mPT) pore and medicinal plants contain phytochemicals that modulate the mPT pore. Hypothesis and Purpose: We investigated the modulatory effects of crude methanol extract of Daniellia oliveri leaves (CMDO) on mPT pore in vitro. Study Design and Methods: Phytochemical screening and antioxidant activities of crude methanol extract of Daniellia oliveri leaves (CMDO) were evaluated accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Studies have attributed the antioxidative potential of medicinal plants to the presence of antioxidative phytochemicals such as flavonoids and phenols [32,33]. Since MFDO induced mitochondrial mPT pore opening, enhanced mitochondrial F 1 F 0 ATPase and inhibited mitochondrial lipid peroxidation in vitro [16], the influence of MFDO on antioxidant enzymes and apoptotic biomarkers were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have attributed the antioxidative potential of medicinal plants to the presence of antioxidative phytochemicals such as flavonoids and phenols [32,33]. Since MFDO induced mitochondrial mPT pore opening, enhanced mitochondrial F 1 F 0 ATPase and inhibited mitochondrial lipid peroxidation in vitro [16], the influence of MFDO on antioxidant enzymes and apoptotic biomarkers were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on the crude methanol extract of the plant revealed the presence of several phytochemicals and also that MFDO leaves is the most potent of all solvent fractions in the induction of mitochondrial permeability transition pore (mPT), enhancement of mitochondrial F 1 F 0 ATPase activity and inhibition of mitochondrial lipid peroxidation in rat liver in vitro [16]. It is in view of this preliminary study that further investigation on the influence of MFDO on antioxidant enzymes and apoptotic biomarkers were carried out on rat liver.…”
Section: Introductionmentioning
confidence: 99%
“…The use of plants as medicine has been well documented over the years, and with availability of modern equipment and means of analyses, the active principles of these plants have been isolated, and their therapeutic potential described, leading to the development of drugs (14). Earlier studies have reported the modulatory effect of plants on MPTP opening, usually triggered by Ca 2+ (15)(16)(17). This modulatory effect is usually ascribed to the presence of health promoting bioactive compounds in the plants.…”
Section: Introductionmentioning
confidence: 99%